Combining dc and ac electrochemical characterization with micro Raman analysis on industrial DSCs under accelerated thermal stress. (1st May 2018) - Hu, Jiangang; Kontos, Athanassios G.; Georgiou, Charalambos Andrew; Bidikoudi, Maria; Stein, Nir; Breen, Barry; Falaras, Polycarpos
Abstract: Dye Sensitized Solar Cells (DSCs) have achieved high power conversion efficiencies at a low cost. However, high stability remains an issue that impedes their commercialization and their degradation mechanisms are still under debate. In this study, we focus on accelerated thermal stressing of industrial DSCs at 85 °C for up to 290 h. The overall reduction of the DSCs efficiency ( η ) under this harsh stress is relatively small (about 20%) due to nearly 10% decrease in the Short Circuit Current (Jsc ) and Open Circuit Voltage (Voc ) and mainly occurs in the initial stage (within the first 54 h). The ageing mechanism is studied by combining the electrical, dc ( J - V ) and ac (impedance) characterization of the cells with their in - situ spectroscopic analysis under bias by micro-Raman. A sharp decrease in the recombination resistance at the sensitized photoelectrode/electrolyte interface is identified for the aged cell which is ascribed to trapping of triiodide species in the photoelectrode and accounts for the Voc drop of the cells. Jsc reduction could be justified by mitigation in the electron collection efficiency. Graphical abstract: Highlights: Accelerated thermal stress of industrial DSC modules at 85 °C for up to 290 h. Small overall reduction (about 20%) of DSC efficiency at 92% solar irradiance. Ageing results in enhanced recombination rates during the first 54 h of stress. Modules behavior accessed by impedance and micro Raman spectroscopies. Recombination resistance and intensity of Raman bands show similar bias dependence.